HUBUNGAN PERSONAL HYGIENE DENGAN RIWAYAT SKABIES DI DAYAH INSAN QUR’ANI ACEH BESAR - Zuheri Zuheri; Amira Balqis SRG (Jurnal Sains Riset, 2021)
Scabies is a skin disease caused by a mite known as the Sarcoptes scabiei, is in the Arachnida class. Scabies can spread very easily through direct contact by sharing clothing, bed sheets, towels, pillows or mattresses. This study aimed to determine the relationship between personal hygiene with a history of scabies in Dayah Qur'ani Aceh Besar in 2019. This research method uses cross sectional analytic design with cross sectional approach. The number of sample is 88 students who were willing to become respondents and were present at the time of the study. Data were analyzed with Chi-Square analysis. The result of this study showed that there were 2 children (25%) with good personal hygiene and 6 children (75%) with bad personal hygiene were affected by scabies, 35 children (43.8%) with good personal hygiene and 45 children (56.2%) with bad personal hygiene were not affected by scabies. From the statistical test showed that there is no correlation between personal hygiene and the occurrence of scabies, p value = 0.306.Keywords: Scabies, Personal Hygiene